2020
DOI: 10.3390/cells9020280
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Bone Morphogenetic Protein 7 (BMP-7) in Inflammation in Heart Diseases

Abstract: Bone morphogenetic protein-7 is (BMP-7) is a potent anti-inflammatory growth factor belonging to the Transforming Growth Factor Beta (TGF-β) superfamily. It plays an important role in various biological processes, including embryogenesis, hematopoiesis, neurogenesis and skeletal morphogenesis. BMP-7 stimulates the target cells by binding to specific membrane-bound receptor BMPR 2 and transduces signals through mothers against decapentaplegic (Smads) and mitogen activated protein kinase (MAPK) pathways. To date… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 251 publications
(317 reference statements)
4
41
0
Order By: Relevance
“… 10 , 27 , 48 This is highlighted by BMP7-driven attenuation of chondrocyte COX-2, IL-6, and PGE 2 levels in the present work, with similar actions for peptides p[63−82] and p[113−132]. BMP7 has previously also been reported as a morphogen with anti-inflammatory properties in other tissues and cell types like kidney, 49 heart, 50 blood vessels, 50 and macrophages. 51 The observation that these peptides attenuate PGE 2 release from intra-articular tissue other than cartilage (IPFP, meniscus, and not significantly from synovium) is in line with the previously reported tissue-wide anti-inflammatory actions of BMP7.…”
Section: Discussionsupporting
confidence: 78%
“… 10 , 27 , 48 This is highlighted by BMP7-driven attenuation of chondrocyte COX-2, IL-6, and PGE 2 levels in the present work, with similar actions for peptides p[63−82] and p[113−132]. BMP7 has previously also been reported as a morphogen with anti-inflammatory properties in other tissues and cell types like kidney, 49 heart, 50 blood vessels, 50 and macrophages. 51 The observation that these peptides attenuate PGE 2 release from intra-articular tissue other than cartilage (IPFP, meniscus, and not significantly from synovium) is in line with the previously reported tissue-wide anti-inflammatory actions of BMP7.…”
Section: Discussionsupporting
confidence: 78%
“…In addition, the KEGG pathway analysis of these differentially expressed genes showed that the top three signal pathways with the largest number of enriched genes were the TNF signaling pathway, osteoclast differentiation, and Toll-like receptor signaling pathway (Figure 2B). All these pathway enrichments were also supported and echoed by corresponding literature (13,27,28).…”
Section: Verification and Functional Analysis Of Differentially Expressed Genes In Acute MIsupporting
confidence: 85%
“…Five viral miRNAs were predicted to act in synergy to regulate 2 genes (BMP7 and CD36) out of 4 significantly down-regulated genes related to immune and apoptotic functions. Previous studies reported that BMP-7 is associated with pathophysiology of several diseases[ 48 ]. Recent evidence suggested that antagonists of BMP signaling pathways may play critical role in the treatment of COVID-19 induced multi-organ failure[ 49 ].…”
Section: Discussionmentioning
confidence: 99%